WIDMIR News Media Articles 2004 - (:unkn) unknown (My University, 2004)
The news media articles pertain to the early development of the Wisconsin Institutes for Discovery and are dated to the year 2004. Keywords include: state stimulus; research; technology; Jim Doyle; Carl Gulbrandsen.